Heat transfer performance of a novel PCM based heat sink coupled with heat pipe: An experimental study - Shailesh, K.; Naresh, Y.; Banerjee, J. (Applied thermal engineering, 2023)
Thermal management is vital for all electronic applications due to the system’s considerable heat output. The improvement of the charging time for a continuous operation has been the subject of much research to date. However, for intermittent operations, which are most likely to be experienced in practical applications are considered, a reduction in the heat discharge time from the heat sink is equally as essential as an improvement in the charging time. The main aim of this study is to develop a strategy that enhances the charging cycle performance and performs well during the discharging cycle as well. This paper reports the experimental heat transfer results of a novel n-Eicosane phase change material (PCM) based finned heat sink coupled with a heat pipe for electronic thermal management. Heat transfer experiments are performed on four heat sink (HS) configurations: heat sink (i) without a fin, (ii) with a circular stem at the center, (iii) with three longitudinal plate fins having a central gap for heat pipe provision, and (iv) with four longitudinal plate fins. A circular heat sink having an outer diameter of 58 mm and 55 mm in height with a wall thickness of 4 mm is considered for all the heat sink configurations. The fill ratios considered are 33, 66, and 99%. The heat input given to the plate heater is varied between 8 and 12 W. Results show that the HS performs best at a PCM fill ratio of 99%. A sintered heat pipe is coupled with a three fin heat sink. Finned heat sink with heat pipe (FHSHP) enhances the (i) charging time by 21.1%, 15.41%, and 21.65%, (ii) discharging time by 22.5%, 23.25%, and 21.25% compared to a heat sink with three fins for the power level of 8, 10, and 12 W, respectively. Further, the overall effectiveness is high for the FHSHP compared to all the geometries considered in the present study. The novel design (FHSHP) is advantageous from an engineering standpoint for efficient thermal management of electronic components. •Heat transfer experiments are conducted on different PCM based heat sinks.•A heat pipe is coupled to a three-fin heat sink.•An FHSHP shows better performance over all the configurations considered.•Effect of modified Stefan number to reach setpoint temperature is investigated.